Automated Medication Error Risk Assessment System (Auto-MERAS). Issue 1 (January 2018) - Kang, Min-Jeoung; Jin, Yinji; Jin, Taixian; Lee, Sun-Mi
Abstract : This study developed the Automated Medical Error Risk Assessment System (Auto-MERAS), which was incorporated into the electronic health record system. The system itself maintained high predictive validity for medication errors at the area under the receiver operating characteristic curves of above 0.80 at the time of development and validation. This study has found possibilities to predict the risk of medication errors that are sensitive to situational and environmental risks without additional data entry from nurses. Abstract : Supplemental Digital Content is Available in the Text.